Ameaças, controle, esforço e descontentamento do usuário no comportamento seguro em relação à segurança da informação - Klein, Rodrigo Hickmann (2014)
The popularization of softwares intended to mitigate the threats to Information Security ended up producing an incorrect notion that such artifacts can protect organizations from attack and overcome any threat. This mistaken notion may be caused by obtaining partial information on the subject or the lack of adequate awareness, being a human factor that can cause increased vulnerability, because induce a reckless behavior of users in relation to Information Systems. However, only the misconception regarding the perception of the threat and its severity does not justify the in Information Security breaches caused by human factors. Another important insight is the perceived exertion of performing actions that lead to responsible behavior in relation to Information Security, which added to aspects such as indifference to the rules of information security and human error can also be inducing factors of vulnerability and breaches in Information Security. In the present study we opted for the grounding in theories on Information Security through a behavioral approach to the user. The combination of the key concepts of these theories, previously validated in their research and applied to the present study approach, was used in order to understand the extent to which human perception of threat, stress, and disgruntlement control can induce responsible behavior before the Information Security and how that human behavior can generate vulnerability and potential breaches in Information Security. The results showed that there is an influence of Information Security orientation, provided by organizations in the perception and severity of the threat. Furthermore, by applying the linear regression technique, it was verified the relationship between disgruntlement and in relation to Information Security Safe Behaviour. Based on these findings contributions to the academic and practioneer knowledge were developed